2002
DOI: 10.1002/jbm.10112
|View full text |Cite
|
Sign up to set email alerts
|

Heparin‐like polymers modulate proinflammatory cytokine production by lipopolysaccharide‐stimulated human monocytes

Abstract: The search for heparin-like materials remains an intensive field of research. In this context, we studied the immunomodulatory properties of semisynthetic dextran derivatives and naturally occurring sulfated polysaccharides present in brown seaweed (fucans). In this study, we investigated the functional potencies of fucan and dextran derivatives by analyzing their effects on the release of proinflammatory cytokines by resting or lipopolysaccharide (LPS)-stimulated human monocytes and their interactions on mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Many fucans have the property of inhibiting the synthesis of cytokines, such as a fucan extracted from Ascophyllum nodosum , which has the ability to modulate the production of TNF-α and IL-6 when stimulated with lipopolysaccharides (LPS) [29]. Therefore, in order to understand the mechanism of leukocyte migration evoked by F2.0v, we evaluated the effect of this fucan in cytokine (TNF-α, interleukin 1β (IL-1β) and interleukin 6 (IL-6)) release.…”
Section: Resultsmentioning
confidence: 99%
“…Many fucans have the property of inhibiting the synthesis of cytokines, such as a fucan extracted from Ascophyllum nodosum , which has the ability to modulate the production of TNF-α and IL-6 when stimulated with lipopolysaccharides (LPS) [29]. Therefore, in order to understand the mechanism of leukocyte migration evoked by F2.0v, we evaluated the effect of this fucan in cytokine (TNF-α, interleukin 1β (IL-1β) and interleukin 6 (IL-6)) release.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that heparin anti-inflammatory effect could be produced by the inhibition of NF-κ≡ nuclear translocation into the lung, 18 26 reducing the expression of TNF-α and IL-6. 25 28 31 This is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…25 Heparin was also found to inhibit the nuclear factor kappa B (NF-κ≡) pathway in monocytes treated with LPS. 26 27 Furthermore, data recently obtained by our group showed that after LPS injury in human alveolar macrophages heparin limited the expression of TNF-α and IL-6, while in human alveolar type II cells heparin inhibited the NF-κ≡ pathway and their effectors IL-6, MCP-1 and IL-8. 28…”
Section: Introductionmentioning
confidence: 91%
“…In addition, O-desulfated heparin prevented dysfunction of endothelialdependent coronary relaxation following ischemic injury and inhibited translocation of the proinflammatory transcription nuclear factor-jB (NF-jB) from the cytoplasm to the nucleus in human endothelial cells and decreased NF-jB DNA binding in human endothelium and ischemic-reperfused rat myocardium [16]. Recently, fucan and dextran derivatives and heparin were found to modulate, in a dose-dependent manner, the release of proinflammatory cytokines by resting or LPSstimulated human monocytes and to interact with monocyte surfaces by inhibiting LPS-binding to monocyte membranes [17].…”
Section: Introductionmentioning
confidence: 99%